Risk Return Analysis of FTSE Listed Select Stocks with FTSE100 Index - ARINDAM BANERJEE (STIE Malangkucecwara, 2023)
This paper analyses the stock returns of FTSE 100 and a sample of selected companies within the index to determine the existence of interdependence and magnitude of the same. The companies are selectively chosen from certain primary sectors based on their influence on the economy. The idea is to understand if large firms have significant effect on the index. The study involves statistical analysis representing data over a 10-year period spanning 1st November 2011 to 31st October 2021), the data points include adjusted closing values of the index and the selected companies. Correlation and regression analysis is performed by taking the index as the dependent variable and the companies as the independent variable. The results are then analyzed from a variety of perspectives including Skewness, Kurtosis, Correlation Coefficients and Coefficient of Determination. Skewness and Kurtosis reveals the performance of returns as compared to the average. The results of the study reveal a net positive correlation is observed between the index and the companies. additionally, the regression analysis results showcase how certain sectors like defense have a significant relation with the index while others like supermarkets do not. Other interesting facts uncovered relate to how a certain cluster of firms compare as opposed to a single firm when analyzed in conjunction with the index. The results are summarized to come up with a conclusion on the relationship an index has with its constituents.